Fӧrvaret - Persson, Anna (Sweden : RåFILM, 2015)
'Detained' is an absorbing observation from within the walls of a Swedish immigration detention center for rejected asylum seekers. The film follows detainees and staff over the course of one summer. A mother separated from her sons faces deportation, a young man waits for his life to begin, and staff members struggle with the impersonal code of conduct required of their job. With great sensibility to its characters and environment, 'Detained' depicts the silent psychological horror faced by those held in modern detention centers and questions this crucial, global phenomenon.
Verzio Film Festival Submission
Keywords: Documentary films